Risk Factors in Rural Female Workers’ Mental Health: From a Group Therapy Perspective - Garay Moffat, Verónica (Revista de Psicología, 2004)
This article shows psychosocial risk factors in the context of psychotherapy of women, who by the specificity of their work, and because of the characteristics of the type of family they belong, require an analysis of the problematic situation from a more participative approach, with an emphasis on self management, gender and human development. In the present reviews, several authors refer to therapy that stresses the reconstruction of lost identity, frequently referred to as “static entity”, which we approach from a traditional system.